(untitled) (Journal of Parents and Teachers, 2014)
Passages from the works of poets such as Federico García Lorca, Charles Baudelaire, Pablo Neruda and Juan Ramón Jiménez, among others. All the passages have to do with the senses: hearing, sight, taste, touch, and smell.